2011
DOI: 10.1186/ar3523
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of saliva: a unique tool to distinguish primary Sjögren's syndrome from secondary Sjögren's syndrome and other sicca syndromes

Abstract: IntroductionA growing interest has arisen in salivary proteomics as a tool for the identification of biomarkers for primary Sjögren's syndrome (pSS). Nonetheless, only a limited number of preclinical validation studies have been performed, limiting the possibility of translating proteomic results into clinical practice. The primary aim of this study was to refine the diagnostic power of a panel of candidate salivary biomarkers described in pSS with respect to both healthy volunteers and pathological controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 32 publications
7
94
1
1
Order By: Relevance
“…This is in contrast to the results from Baldini et al 19 but similar to that reported by Asashima et al 5 Unlike other investigators, 5,18 we only included patients with sicca symptoms, since the idea behind our study was to develop an additional tool to benefit in the diagnosis of those in whom SS is suspected (i.e., in those with sicca symptoms). In our study, fibromyalgia was more common in those with sicca symptoms but no autoimmune disease (snSS group).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This is in contrast to the results from Baldini et al 19 but similar to that reported by Asashima et al 5 Unlike other investigators, 5,18 we only included patients with sicca symptoms, since the idea behind our study was to develop an additional tool to benefit in the diagnosis of those in whom SS is suspected (i.e., in those with sicca symptoms). In our study, fibromyalgia was more common in those with sicca symptoms but no autoimmune disease (snSS group).…”
Section: Discussioncontrasting
confidence: 56%
“…Our snSS group represents such patients. Baldini et al 19 also included a snSS group in their study. Specifically addressing this point, the ROC curve analysis showed an area under the curve of 0.648 (95% CI: 0.559-0.730, p=0.0023) with an optimal cutoff value of 0.638 ng/mL (not shown in Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Although the principle is simple, this method is not very successful, simply because many eukaryotic cells secrete proteins that are intensely posttranslationally modified. [40][41][42][43][44][45][46][47] Therefore, a peak in the MALDI-MS spectrum does not represent a protein or a peptide but rather a posttranslationally modified protein (or peptide). [45][46][47] However, even if the differences detected are not at the "naked" protein level, the differences observed may still be detected and the proteins responsible for them can be identified.…”
Section: Top-down Secretomicsmentioning
confidence: 99%
“…Catalytically active salivary amylase has been reported to bind to microorganisms and tooth enamel, and as such is perhaps crucial in mediating adherence of pathogens to oral surfaces, and allowing microbial growth through provision of glucose from the breakdown of dietary glucose polymers [7][8][9][10]. Changes in the levels of salivary amylase have been reported in many proteomic studies, including implications in periodontitis [3], Sjögrens Syndrome [5,11], sensory perception of bitter tastes [12], and in binding of salivary tannins [13][14][15][16]. It has also been reported that α-amylase is subject to a very high level of posttranslational modification.…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of this variability is crucial for homeostasis of the oral cavity and hence in oral health. Alterations in the protein composition of saliva have also been associated with diverse diseases, including periodontitis [3], oral cancers [4], and autoimmune diseases such as Sjögrens Syndrome [5]. The changes in salivary protein composition observed in these states may contribute to the progression of these conditions, and may also be of use for identification of biomarkers for disease prognosis or diagnosis [2].…”
Section: Introductionmentioning
confidence: 99%